2007
DOI: 10.1152/ajpcell.00093.2006
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical strain regulates syndecan-4 expression and shedding in smooth muscle cells through differential activation of MAP kinase signaling pathways

Abstract: Julien MA, Wang P, Haller CA, Wen J, Chaikof EL. Mechanical strain regulates syndecan-4 expression and shedding in smooth muscle cells through differential activation of MAP kinase signaling pathways. Am J Physiol Cell Physiol 292: C517-C525, 2007. First published July 5, 2006; doi:10.1152 doi:10. /ajpcell.00093.2006 belongs to a family of transmembrane proteoglycans, acts as a coreceptor for growth factor binding as well as cell-matrix and cell-cell interactions, and is induced in neointimal smooth muscle cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 39 publications
2
14
1
Order By: Relevance
“…The observed decrease in cell-associated syndecan-4 levels after 8 h cytomix stimulation may be the result of shedding of the newly synthesized protein as shedding continued to increase for 8 h following cytomix treatment. These findings reflect those found for the effects of mechanical strain on vascular smooth muscle cells where syndecan-4 expression peaks by 4 h but drops below baseline, unstrained levels by 24 h (26).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The observed decrease in cell-associated syndecan-4 levels after 8 h cytomix stimulation may be the result of shedding of the newly synthesized protein as shedding continued to increase for 8 h following cytomix treatment. These findings reflect those found for the effects of mechanical strain on vascular smooth muscle cells where syndecan-4 expression peaks by 4 h but drops below baseline, unstrained levels by 24 h (26).…”
Section: Discussionsupporting
confidence: 85%
“…Various stimuli have been shown to induce syndecan shedding such as mechanical strain (26,33), insulin (46), thrombin (49), epidermal growth factor (49), and the phorbol ester PMA from a variety of cell types (15). Very recently the proinflammatory cytokines IFN␥ and TNF-␣ were also shown to stim-ulate syndecan-1 and -4 shedding from lung epithelial cells (44).…”
Section: Discussionmentioning
confidence: 99%
“…In a normal aorta, SMC are aligned in the media of the artery, and subjected to mechanical stretch via pulsatile blood flow. Mechanical stretch was found to modulate SMC alignment, differentiation, migration survival/apoptosis as well as its secretion [26] through activating intracellular signaling pathways, including JNK [6], Rho-associated kinase/ROCK, NF-κB-inducing kinase [27], MAPK/ERK kinase (MEKK) [28] etc. Importantly, mechanical stretch induced MP production is ER stress dependent as we have previously shown that elevated mechanical stretch induces apoptosis of SMC in an ER stress-dependent fashion [4].…”
Section: Discussionmentioning
confidence: 99%
“…The myocyte yield was ~90%, which was comparable between the two groups. Isolated cardiomyocytes were then cultured in a culture medium M199 supplemented with or without the α-adrenergic agonist phenylephrine (20 µM) [23] in the absence or presence of the antioxidant N-acetylcysteine (NAC, 500 µM) [24] the mixed α/β adrenergic antagonist carvedilol (100 nM) [25], the β-adrenergic antagonist propanolol (1 µM) [26], or the specific peptide inhibitor for JNK (JNKI, 2 µM) [27]. A cohort of cardiomyocytes was transfected with the SERCA2a adenovirus or the viral vector encoding the marker gene β-galactosidase (β-GAL) at the viral concentration of 10 8 pfu/ml for 36 hrs [28,29] where exposure of phenylephrine was initiated after 18 hrs.…”
Section: Methodsmentioning
confidence: 99%